2019
DOI: 10.1186/s12984-019-0577-x
|View full text |Cite
|
Sign up to set email alerts
|

Fore-aft resistance applied at the center of mass using a novel robotic interface proportionately increases propulsive force generation in healthy nonimpaired individuals walking at a constant speed

Abstract: Background Past studies have utilized external interfaces like resistive bands and motor-generated pulling systems to increase limb propulsion during walking on a motorized treadmill. However, assessing changes in limb propulsion against increasing resistance demands during self-controlled walking has not been undertaken. Purpose We assessed limb propulsion against increasing fore-aft loading demands by applying graded fore-aft (FA) resistance at the center of mass duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…In agreement with our results, previous studies on resistance and uphill walking at constant speeds, non-impaired individuals scale their peak propulsion forces and duration of propulsion according to the degree of resistance or level of inclination against which they are walking ( Lay et al, 2007 ; Ellis et al, 2014 ; Naidu et al, 2019 ). For instance, Naidu et al (2019) assessed limb propulsion generation in healthy participants against increasing backward-directed resistance at the COM while participants were walking at their CWS in an intent-driven treadmill environment. By conducting this study, they observed a proportional increase in the propulsion generation by incrementing backward resistance without significant changes in vertical limb loading.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In agreement with our results, previous studies on resistance and uphill walking at constant speeds, non-impaired individuals scale their peak propulsion forces and duration of propulsion according to the degree of resistance or level of inclination against which they are walking ( Lay et al, 2007 ; Ellis et al, 2014 ; Naidu et al, 2019 ). For instance, Naidu et al (2019) assessed limb propulsion generation in healthy participants against increasing backward-directed resistance at the COM while participants were walking at their CWS in an intent-driven treadmill environment. By conducting this study, they observed a proportional increase in the propulsion generation by incrementing backward resistance without significant changes in vertical limb loading.…”
Section: Discussionsupporting
confidence: 93%
“…We also found that walking against greater backward resistance resulted in greater trailing limb angle, which increased to a greater extent for the slower limb than for the faster limb. According to studies on resistance and uphill walking at constant speeds, healthy, non-impaired individuals modulate their peak propulsion forces and duration of propulsion according to the amount of resistance or level of inclination against which they are walking ( McGowan et al, 2009 ; Franz and Kram, 2014 ; Naidu et al, 2019 ). However, none of these studies have evaluated the amount of each limb’s propulsion generation contribution while each limb moves at a distinctly different speed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations